2019
DOI: 10.1186/s13071-019-3824-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of multiplex Onchocerca volvulus peptide ELISA in non-endemic tropical regions

Abstract: BackgroundCurrently, serodiagnosis of infection with the helminth parasite Onchocerca volvulus is limited to the Ov-16 IgG4 test, a test that has limited sensitivity and suboptimal specificity. In previous studies, we identified several linear epitopes that have the potential to supplement the diagnostic toolbox for onchocerciasis.MethodsIn this study three peptides, bearing in total six linear epitopes were transferred to a multiplex ELISA platform. This multiplex ELISA was used to assess the clinical utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…In our previous work on clinical utility testing of peptide biomarkers, we came to a similar observation when investigating this population of children in Kenya [39]. More than 50% of the children were indeed seroreactive to the peptide epitopes, without presenting any evidence for being infected, or being exposed, or residing in an endemic area.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 60%
See 2 more Smart Citations
“…In our previous work on clinical utility testing of peptide biomarkers, we came to a similar observation when investigating this population of children in Kenya [39]. More than 50% of the children were indeed seroreactive to the peptide epitopes, without presenting any evidence for being infected, or being exposed, or residing in an endemic area.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 60%
“…No significant difference between the non-infected and different infection groups was observed (P χ 2 = 0.7042), suggesting that none of these intestinal parasites are linked to elevated CCG levels. The urine CCG data were also compared with the peptide serology data previously obtained from the same study population [ 39 ]. None of the 3 peptide markers correlated with urine CCG, with P-values from Chi square analysis ranging from 0.2362 to >0.999 ( Fig 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has proven a successful approach for viral diseases like HIV and HCV [ 59 61 ]. However, our current data seem to indicate that it will not be as straightforward for helminth parasites [ 58 ]. It seems difficult to use antibody detection against linear epitopes as a good measure of helminth or parasite exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A similar discussion on the need for well-characterized biobanks has also been made for O. volvulus. Several peptides were identified that were assumed to be linked to O. volvulus infection but were later found to be linked-at least partly-to other immunogens, possibly from parasitic origin [58].…”
Section: There Is a Need For Well-characterized Biobanks For Biomarker Discoverymentioning
confidence: 99%